THE ROLE OF TRANSLATION IN DIPLOMACY AND INTERNATIONAL RELATIONS (Ustozlar uchun, 2026)
Translation plays a pivotal role in diplomacy and international relations, acting as both a practical tool for communication and a strategic instrument for fostering mutual understanding among nations. This article explores the ways in which translation facilitates dialogue, negotiation, and the exchange of political, legal, and cultural knowledge across linguistic boundaries. In diplomatic contexts, accuracy, nuance, and cultural sensitivity are essential, as mistranslation can have serious consequences for international cooperation and conflict resolution. Drawing on theoretical frameworks from Translation Studies, as well as case studies from international organizations and bilateral negotiations, the article examines the skills and strategies employed by professional translators and interpreters in high-stakes environments. Special attention is given to the translation of political discourse, treaties, speeches, and diplomatic correspondence, highlighting the challenges posed by idiomatic expressions, culturally specific references, and strategic ambiguity.